Perjanjian Nominee dan Akibat Hukumnya Menurut Sistem Hukum Positif Indonesia - Linda Vianty Mala Takko; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi (Warmadewa Press, 2021)
The procedure for transferring land rights to house ownership or those occupied by foreigners residing in Indonesia has been regulated by a ministerial regulation or the head of the land agency which is carried out by the process of registering the land with the aim of providing legal certainty or providing legal protection for those who have rights over land. A plot of houses and land, units of apartment or other rights owned so that it is easy to prove that it is true that they are the owner of these rights. The purpose of this study is to determine the procedures for the release or transfer of rights to the ownership of a residential or residential house by foreigners domiciled in Indonesia. The research used is a type of normative legal research. Regarding the source of legal materials used, it is divided into primary legal materials, which are the main legal materials which are the basis for the study of the writing of this research. From the presentation of the research it can be concluded that the procedures for the transfer of rights to land for permanent residential ownership by foreigners who are domiciled in Indonesia have been regulated by the ministerial regulation or the head of the land agency which is carried out by the process of registering the land with the aim of providing legal certainty or providing legal protection for who has the right to a plot of house and land, unit of apartment or other rights owned so that it is easy to prove that it is true that it is the owner of these rights.